Structural characteristics of organic dairy farms in four European countries and their association with the implementation of animal health plans. (July 2019) - Blanco-Penedo, Isabel; Sjöström, Karin; Jones, Philip; Krieger, Margret; Duval, Julie; van Soest, Felix; Sundrum, Albert; Emanuelson, Ulf
Abstract: The aim of the present study was to classify the diversity of organic dairy farms in four European countries according to their structural characteristics and investigate the association of these farm types with implementation of herd health plans. A Multiple Correspondence Analysis (MCA), followed by Agglomerative Hierarchical Clustering (AHC), was used to classify the farms. Data for the analysis came from a survey of 192 organic farms from France, Germany, Spain and Sweden and contained farm and farmer descriptions from which the typologies were derived. Herd health plans was agreed for each farm, via a participatory approach involving the farmers, their veterinarians and other advisors (e.g. dairy advisors) by the use of an impact matrix. The MCA yielded two principal component axes explaining 51.3% of variance. Three farm groups were identified by AHC using the factor scores derived from the MCA. Cluster 1, the most numerous group (56.7% of the sample), had medium herd sizes with moderate use of pasture and moderate intensity of input use. Cluster 2, representing 17.7% of the sample, were the most extensive system and mainly of very small farm size. Cluster 3 (25.5% of the sample and only found in Sweden), had an intensive management approach, but relatively low stocking rate. The analysis also showed that organic dairy farms adopted differentiated strategies towards economic assets and animal health status, according to group membership. The typology therefore provides insights into the potential for advisory strategies relating to husbandry practices, different housing, pasture management and intensity, etc. adapted to different groups of farms. Regarding herd health plan implementation, Cluster 1 was the group with most implemented actions and Cluster 2 with lowest rate of implemented actions. These results may be used as background for directing (tailored) advice strategies, i.e. different types of organic dairy farms (clusters) may require different types of advisory services and recommendations adapted to the specific farm situation in order to deliver future improvements in animal health. Highlights: Structural analysis of 192 farms and descriptors from which typologies were derived. The three farm clusters and rates of implementation of health actions were explored. The results may be used as a background for tailored advisory service strategies. Different clusters of organic dairy farms needs different type of advisory approach.